1998
DOI: 10.1111/j.1751-0813.1998.tb10158.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of abamectin and two formulations of ivermectin on the survival of larvae of a dung‐breeding fly

Abstract: The oral formulation of ivermectin is eliminated more rapidly than the injectable formulation and, as a consequence, is likely to be less harmful to dung-feeding insects. Abamectin and ivermectin appear to equally toxic larvae of M vetustissima.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Similar assays with M. vetustissima [174], M. autumnalis [175-176], and M. domestica [174] detected lethal effects for 28 to 35, 14 to 28, and 7 to 14 days, respectively. Treatment of cattle with an injectable formulation of 200 µg IVM kg -1 body weight inhibited larval growth and prevented emergence of adults of Musca domestica (house fly) [174, 177-178] and M. vetustissima (bush fly) [155-156] for 7-14 days post-treatment. An oral drench of 200 µg IVM kg -1 live weight to sheep prevented emergence of M. vetustissima for the first 4-6 days post-treatment of animals, with 100% survival at day 28 [100], and delayed reproductive development of Lucila cuprina (sheep blowfly) [169-170].…”
Section: Ecotoxicity Of Avermectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar assays with M. vetustissima [174], M. autumnalis [175-176], and M. domestica [174] detected lethal effects for 28 to 35, 14 to 28, and 7 to 14 days, respectively. Treatment of cattle with an injectable formulation of 200 µg IVM kg -1 body weight inhibited larval growth and prevented emergence of adults of Musca domestica (house fly) [174, 177-178] and M. vetustissima (bush fly) [155-156] for 7-14 days post-treatment. An oral drench of 200 µg IVM kg -1 live weight to sheep prevented emergence of M. vetustissima for the first 4-6 days post-treatment of animals, with 100% survival at day 28 [100], and delayed reproductive development of Lucila cuprina (sheep blowfly) [169-170].…”
Section: Ecotoxicity Of Avermectinsmentioning
confidence: 99%
“…Due to strong binding of IVM to soil [214] and, thus, little potential for transport from the terrestrial to the aquatic compartment, no risk for aquatic organisms was indicated in previous environmental risk assessments of IVM [74, 120, 156]. As a result, very few studies have been undertaken to examine the adverse impacts of exposure to IVM on freshwater organisms.…”
Section: Ecotoxicity Of Avermectinsmentioning
confidence: 99%
“…, 1993; Strong & James, 1993; Strong et al. , 1996; Wardhaugh & Mahon, 1998; Floate, 1999; Errouissi et al. , 2001; Wardhaugh et al.…”
Section: Environmental Effectsmentioning
confidence: 99%
“…Wardhaugh and Mahon [33] in Australia observed that injectable formulation of abamectin and ivermectin appear to be equally toxic for larvae of Musca vetustissima, while the oral formulation of ivermectin seems to be less harmful. Strong et al [25], working with cattle dung following the administration of ivermectin sustained-release boluses, conclude that residues prevent fauna colonisation 3-weeks after administration.…”
Section: Differences Between Endectocides For Residue Toxicitymentioning
confidence: 99%
“…Non-target and target Diptera larvae, which in some seasons are very important to dung aeration, react negatively but not in the same way to endectocides. Nematocerous Diptera are able to tolerate dung, 10 days after treatment, while Cyclorrapha [16] or Musca vetustissima, Musca domestica, and Haematobia irritans [33], remain at risk for a period of 30-35 days. These avermectin effects range from acute or chronic mortality by paralysis and feeding or growth and moulting interference [23], or sublethal and long-term consequences like reproductive deficiencies [14] or external structural abnormalities [6].…”
Section: Effects On Dung Arthropodsmentioning
confidence: 99%